Analisis Deskriptif Dan Akar Permasalahan Kurangnya Disiplin Serta Rendahnya Sikap Toleransi Beragama Siswa Di Kelas V B SDN 50 Pelangi - Fuji Syahfitrah Oihu; Santika Safitri; Nesti Juniarsi; Yuyun, Yuyun; Nassarudin, Nassarudin; Asmina, Asmina; Haliadi, Haliadi (Jurnal Sultra Elementary School, 2026)
This study aims to describe the disciplinary behavior and religious tolerance of fifth-grade students at SDN 50 Pelangi and the factors influencing them. The study used a descriptive qualitative approach, with data collection techniques including participant observation, interviews, and documentation studies. The results indicate that student discipline remains low, characterized by tardiness, neglect of assignments, and classroom disruption, which impacts the quality of social interactions and academic achievement. Furthermore, religious tolerance is also suboptimal, evident in verbal teasing and social exclusion among peers. An analysis of causal factors indicates a link between student behavior and family parenting styles, consistent enforcement of school rules, and peer influence. Supporting an inclusive school environment, implementing a character-based curriculum, collaborative activities across groups, and counseling have proven effective in fostering discipline and tolerance. This study emphasizes the importance of synergy between families, teachers, and peers in shaping positive behavior. With a systematic and contextual approach to character education, schools can create a disciplined, inclusive, and harmonious learning environment, enabling students to develop not only academically but also to become individuals with noble character and be prepared to face social challenges.